IMPLEMENTASI MEDIA TIKTOK EDUKATIF UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS III SD SURABAYA - Arifiyanti Isnainingrum, Miftakhul; Thamrin Hidayat, Muhammad; Lutfauziah, Asmaul; Wahyudi, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes in Social and Natural Sciences (IPAS) among third-grade students at SDN Siwalankerto II Surabaya, which were caused by the use of less engaging learning media and the suboptimal utilization of digital technology in the learning process. This condition resulted in students being less enthusiastic during lessons, thereby affecting their understanding of the material. The study aimed to determine the improvement of students’ IPAS learning outcomes after the implementation of educational TikTok media on the topic of cardinal directions. This study employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest-Posttest Design model. The sample consisted of 30 students from class III C selected through purposive sampling. Data were collected through learning outcome tests and student response questionnaires. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed Rank Test. The results showed that the average pretest score of 44.19 increased to 92.58 on the posttest. Students’ responses to the use of educational TikTok media were categorized as very good. The Wilcoxon Signed Rank Test yielded a Z value of -4.850 and an Asymp. Sig. (2-tailed) value of < 0.001, indicating a significant difference in learning outcomes before and after the treatment. Based on the findings, it can be concluded that educational TikTok media is effective in improving IPAS learning outcomes among third-grade students at SDN Siwalankerto II Surabaya and can serve as an innovative learning medium to support the teaching and learning process in elementary schools.